Impact of ICT on privacy and personal data protection in two Malaysian academic libraries - Mohd Roni, Nurul Azurah; Mohd Napiah, Mohd Kamal; Hassan, Basri (2011)
The rapid advance of information and communication technologies (ICT) has permitted the creation of digital libraries. However, the development of the digital library has created certain threats in some aspects especially in terms of privacy and personal data protection which is generally regarded as confidential between the library and the individual. This study aims to investigate the policies, preparedness and awareness of two Malaysian public academic libraries i.e. International Islamic University Malaysia (IIUM) and Universiti Putra Malaysia (UPM) on the issues of privacy and data protection. This study also attempts to discover the library users‘ perceptions with regard to the collection and use of their personal data and to examine the policies and practices adopted by libraries in relation to users‘ privacy. The methods of the study were interview and questionnaires. The library staffs in charged personal data collection from the two public academic libraries were interviewed. Questionnaires were distributed randomly to the library users from the two public academic libraries. The findings showed that the majority of library personnel were aware and observe the privacy and data protection policies in their libraries even though there were no official written statements concerning this subject. They also realized that these issues were still pending in term of implementation at their parent organizations (university) as well as in their libraries. The finding also shows that library users were aware about their privacy and personal data protection and they realize that their privacy and personal data protection were threatened.